Penggunaan Antitrust Immunity dan Kartel di Masa Pandemi - Sheila Namira Marchellia (Jurnal Persaingan Usaha, 2021)
In this situation during Covid-19 pandemic almost every sector in the world was affected by it, and one of them is the economic sector. This condition of covid pandemic made every customer hard to fulfill for their daily needs, and at the end affected the companies. A lot of companies have hard times to compete with other company, and they also must find a way to save themselves from bankruptcies. By using a normative juridical method, This research aims to provide new ideas that can be used as a solution in dealing with similar problems. This research will focus on loosening regulations in Law no. 5 of 1999 that can be a solution to the problems of the economic sector caused by Covid-19. The result of this research found that Antitrust immunity and cartels can help companies, workers, and consumers who are the community itself. However, this mitigation must meet certain conditions, which is as Ultimum remedium, The implementation of Law no. 5 of 1999 will be back to normal when the Covid-19 pandemic is over. During this condition, the Business Competition Supervisory Commission has a very important role in supervising the company. In the end, fair business competition can still be realized.